2018
DOI: 10.1098/rsos.170865
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical studies on curcumin-sophorolipid nanostructures: applications in quorum quenching and imaging

Abstract: Sophorolipid biosurfactants are biodegradable, less toxic and FDA approved. The purified acidic form of sophorolipid is stimuli-responsive with self-assembling properties and used for solubilizing hydrophobic drugs. This study encapsulated curcumin (CU) with acidic sophorolipid (ASL) micelles and analysed using photophysical studies like UV-visible spectroscopy, photoluminescence (PL) spectroscopy and time-correlated single photon counting (TCSPC). TEM images have revealed ellipsoid micelles of approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 67 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Within the nanodisc environment, we also saw increased solubility over curcumin solubilized in water and a similar solubility to curcumin solubilized in DMSO (curDMSO) ( Figure 2 C). Contrary to the yellow fluorescence observed under UV light for curDMSO solutions, our curcumin nanodiscs demonstrate a slight blue shift in fluorescence, indicating incorporation of the curcumin into the lipid nanodisc environment ( Figure 2 C), as has been described previously [ 30 ]. Across three biological replicates, our cNLP formulation yielded an average of 348 µg/mL incorporated curcumin.…”
Section: Resultssupporting
confidence: 80%
“…Within the nanodisc environment, we also saw increased solubility over curcumin solubilized in water and a similar solubility to curcumin solubilized in DMSO (curDMSO) ( Figure 2 C). Contrary to the yellow fluorescence observed under UV light for curDMSO solutions, our curcumin nanodiscs demonstrate a slight blue shift in fluorescence, indicating incorporation of the curcumin into the lipid nanodisc environment ( Figure 2 C), as has been described previously [ 30 ]. Across three biological replicates, our cNLP formulation yielded an average of 348 µg/mL incorporated curcumin.…”
Section: Resultssupporting
confidence: 80%
“…They are an eco-friendly and biocompatible class of amphiphilic biosurfactants that are used in a wide spectrum of medicinal application ranging from biosurfactant, cosmetic and detergent development [ 3 ]. Over the last years biosurfactants in general and SLs specifically have been used in biomedical sciences for their antifungal [ 4 ], antibacterial [ 5 , 6 ] anti-HIV [ 7 ], and anticancer [ 8 , 9 ] properties. The advantage of using SLs against cancer cells lines is their low side effect on normal tissue [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they found that sophorolipids do not show any antibacterial action on PAO1 but only disperse biofilm formation of the bacterial strain [ 110 ]. Vasudevan and Prabhune [ 111 ] evaluated that curcumin-sophorolipid nanoparticles exhibited good antibiofilm activities by quorum quenching against P. aeruginosa [ 111 ].…”
Section: Applications Of Sophorolipids In Food and Healthmentioning
confidence: 99%